1999
DOI: 10.1161/01.hyp.34.5.1141
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Dependent Gene Expression of Egr-1 and PDGF A Regulate Angiotensin II–Induced Proliferation in Human Vascular Smooth Muscle Cells

Abstract: Abstract-We have previously shown, in a neonatal rat cell line, that angiotensin II (Ang II)-induced proliferation in vascular smooth muscle cells is extracellular matrix (ECM) dependent. We hypothesized that such an effect might be mediated via differences in Ang II-induced increases in the transcriptional factor early growth response-1 (Egr-1) gene and, consequently, in platelet-derived growth factor (PDGF). Cultured human newborn aortic smooth muscle cells were studied on 4 different surfaces: (1) plastic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…27 Numerous studies have demonstrated that angiotensin II through AT1 receptor induces VSM cell proliferation and hypertrophy and has an essential role in extracellular matrix expansion. [29][30][31][32] Furthermore, Candesartan and cavernous tissue in SHR JE Toblli et al cell culture, animal models and clinical studies have supported the idea that AT1 receptor activation causes vascular superoxide release in vitro and in vivo leading to impairment of endothelium-dependent vasodilation. 33,34 In agreement with these findings, inhibition of AT1 receptor activation by AT1 receptor antagonist or ACE inhibitors improves endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…27 Numerous studies have demonstrated that angiotensin II through AT1 receptor induces VSM cell proliferation and hypertrophy and has an essential role in extracellular matrix expansion. [29][30][31][32] Furthermore, Candesartan and cavernous tissue in SHR JE Toblli et al cell culture, animal models and clinical studies have supported the idea that AT1 receptor activation causes vascular superoxide release in vitro and in vivo leading to impairment of endothelium-dependent vasodilation. 33,34 In agreement with these findings, inhibition of AT1 receptor activation by AT1 receptor antagonist or ACE inhibitors improves endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Although it is somewhat surprising that a significant arginase induction in coronary microvessels can be achieved within such a short period (ie, 60 minutes) of exposure to H 2 O 2 , previous studies have shown that pharmacological and pathophysiological stimulations can alter the expression of mRNA and/or protein within 60 minutes. [51][52][53][54] Interestingly, our recent studies demonstrated that vascular arginase I was upregulated leading to the impaired NO-mediated dilation in the porcine heart subjected to either chronic hypertension (8 weeks) 55 or an acute episode of ischemiareperfusion. 56 Because ROS, including H 2 O 2 , play an important role in the vascular dysfunction in hypertension 5 and ischemia-reperfusion injury, 7 it is speculated that H 2 O 2 may be the molecule that triggers the overexpression of vascular arginase and consequently leads to the impairment of NOS-mediated vascular function under these pathophysiological conditions.…”
Section: Thengchaisri Et Al Hydrogen Peroxide Impairs Coronary Arterimentioning
confidence: 99%
“…Their studies demonstrate that either cyclic stretch or Ang II treatment increases the proliferation of VSMCs when the cells are plated on collagen, fibronectin, or vitronectin, but not on laminin or elastin; further, these effects require the production of PDGF [41,42]. In addition, the proliferative effect of stretch is abolished by inhibition of β 3 but not β 1 integrin, suggesting a selective effect of β 3 integrin [41].…”
Section: Integrin-ecm Interactions In Mediating the Effects Of Mechanmentioning
confidence: 99%
“…The role of integrins in linking mechanical stimuli with the action of growth factors in VSM was first established by Wilson and colleagues [41,42] using VSMCs exposed to cyclic stretch generated by a Flexercell Stress Unit, a device designed to simulate the distension that VSMCs experience under physiological conditions [43]. Their studies demonstrate that either cyclic stretch or Ang II treatment increases the proliferation of VSMCs when the cells are plated on collagen, fibronectin, or vitronectin, but not on laminin or elastin; further, these effects require the production of PDGF [41,42].…”
Section: Integrin-ecm Interactions In Mediating the Effects Of Mechanmentioning
confidence: 99%